2022
DOI: 10.3389/fgene.2022.661348
|View full text |Cite
|
Sign up to set email alerts
|

Increased ATP2A1 Predicts Poor Prognosis in Patients With Colorectal Carcinoma

Abstract: Colorectal cancer is one of the most common malignant tumors in the digestive system. Traditional diagnosis and treatment methods have not significantly improved the overall survival of patients. In this study, we explored the value of ATP2A1 as a biomarker in predicting the prognosis of colorectal cancer patients. We used the TCGA database to reveal the relationship between ATP2A1 mRNA level and prognosis, methylation, and immune invasion in colorectal cancer. The results showed that the expression of ATP2A1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Zong con rmed that CRC patients with high expression of FOXD1 and Plk2 had a worse prognosis by constructing a Nomogram model (10). It was reported that ATP2A1 is a potential pathogenic factor, and CRC patients with high expression of ATP2A1 have a low survival rate (11). It has also been claimed that CX3CR1 promotes cell proliferation and migration of CRC cells by regulating macrophage polarization (12).…”
Section: Introductionmentioning
confidence: 93%
“…Zong con rmed that CRC patients with high expression of FOXD1 and Plk2 had a worse prognosis by constructing a Nomogram model (10). It was reported that ATP2A1 is a potential pathogenic factor, and CRC patients with high expression of ATP2A1 have a low survival rate (11). It has also been claimed that CX3CR1 promotes cell proliferation and migration of CRC cells by regulating macrophage polarization (12).…”
Section: Introductionmentioning
confidence: 93%